Impaired glymphatic function in relation to cumulative blood glucose exposure: A population-based cohort study - Yufan Zhang; Jing Sun; Sihui Guo; Ying Hui; Xiaoshuai Li; Jing Li; Xinyu Zhao; Pengfei Zhao; Shuohua Chen; Shouling Wu; Zhenchang Wang; Han Lv (IBRO Neuroscience Reports)
Objective: The relationship between prolonged blood glucose exposure and glymphatic system function of the brain remains unknown. This study aimed to investigate the association between cumulative blood glucose levels and neuroimaging metrics associated with glymphatic function. Methods: This study was conducted in a multicenter, community-based cohort study. Magnetic resonance imaging (MRI) data were collected once between 2020 and 2022. The assessment of brain glymphatic function can be conducted using the diffusion tensor imaging analysis along the perivascular space (DTI-ALPS) index. Cumulative fasting blood glucose (FBG) values from 2014 to 2018 were calculated for each participant as a prolonged exposure, while a single measurement of FBG at the same time of MRI acquisition represented a short-term exposure. A generalized linear model was used to evaluate the association of blood glucose exposure and DTI-ALPS index. Results: A total of 251 subjects were included. Prolonged hyperglycemic exposure with FBG ≥ 7.0 mmol/L was significantly associated with lower average DTI-ALPS index (β = -0.058, 95 % confidence interval, -0.096 to -0.019). These findings remained significant among participants over 60 years old and those not taking hypoglycemic medication. No significant associations were observed in single measurement. Conclusion: Prolonged exposure to hyperglycemia is significantly associated with a lower average DTI-ALPS index, potentially playing a crucial role in the impairment of glymphatic function, especially among older adults. A well controlled blood glucose level may demonstrate a protective effect on glymphatic function, indicating better brain health.